MIKA – continuing training provision to promote the media-pedagogical competencies of company-based training staff - Schäfer, Robert [Verfasser] (My University, 2022)
"The digital transformation is both impacting everyday training and work at companies and presenting trainers with new challenges. The continuing training concept “Media and IT competency for training staff (MIKA)” supports trainers with deploying digital technologies in teaching and learning processes and helps them develop personal competencies via guided practically related exercises in face-to-face sessions, webinars and phases of self-directed learning." (author's abstract; BIBB-Doku)
Keywords: P 3.2.1 Ausbilder; L 4.2 Mediengestützte Lehr-Lernformen; S 1.5 Weiterbildung; 370; Ausbilder; Medienkompetenz; digitale Medien; Medieneinsatz; Weiterbildungsangebot